Form follows function?: proposing a blueprint for ecosystem service assessments based on reviews and case studies - Seppelt, Ralf; Fath, Brian D.; Burkhard, Benjamin; Grêt-Regamey, Adrienne; Lautenbach, Sven; Hotes, Stefan; Spangenberg, Joachim H.; Verburg, Peter (Ecological indicators, 2012)
Ecosystem service assessments (ESA) hold the promise of supporting the quantification and valuation of human appropriation of nature and its goods and services. The concept has taken flight with the number of studies published on the topic increasing rapidly. This development, and the variation of diverging approaches, support innovative ideas and may lead to complementary insights from various perspectives. However, at the same time this slows scientific synthesis through increasing uncertainty with respect to the appropriate methodologies to be used to support solving environmental management problems. We analyzed ESA and the underlying concepts based on the variety of available publications and reviews, which revealed a number of different methods, uncertain reliability and robustness. In order to facilitate comparison, evaluation and synthesis of ecosystem service assessments we propose a blueprint for reporting studies in a structured way. By exemplifying this with worked examples, we argue that the use of such a blueprint will (i) assist in achieving improved communication and collaboration in transdisciplinary teams; (ii) reveal methodological aspects, important for the interpretation of results; (iii) support robustness and reliability of assessments; (iv) aid in structuring assessment studies and monitoring programs; (v) provide a base for comparing and synthesizing results of different studies (e.g. in meta-analysis), and thus (vi) provide a base for further implementation of ESA.